2014
DOI: 10.1002/ajim.22334
|View full text |Cite
|
Sign up to set email alerts
|

The changing patterns of psychosocial exposures at work in the South of Europe: Spain as a labor market laboratory

Abstract: Although this study analyzes wage-earner "survivors" after the outbreak of the current economic crisis, it shows a worsening of harmful exposures to some psychosocial risks. In a context of job destruction, concerns about worsening working conditions appear to be subordinate to insecurity about job loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
1
19
1
2
Order By: Relevance
“…Entre las limitaciones del estudio se encuentra que la información se refiere al año 2005, podría no ser adecuado la extrapolación de los datos a la actualidad. En los últimos años, y sobre todo como consecuencia de la crisis económica, las condiciones laborales han empeorado en ciertos aspectos como una mayor inseguridad y una menor autonomía y apoyo de los compañeros 12 . Se debe tener en cuenta además, que MatEmESp contiene información sobre la exposición a factores psicosociales para un número limitado de ocupaciones y que el análisis que permiten Riesgos psicosociales por ocupación en España…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Entre las limitaciones del estudio se encuentra que la información se refiere al año 2005, podría no ser adecuado la extrapolación de los datos a la actualidad. En los últimos años, y sobre todo como consecuencia de la crisis económica, las condiciones laborales han empeorado en ciertos aspectos como una mayor inseguridad y una menor autonomía y apoyo de los compañeros 12 . Se debe tener en cuenta además, que MatEmESp contiene información sobre la exposición a factores psicosociales para un número limitado de ocupaciones y que el análisis que permiten Riesgos psicosociales por ocupación en España…”
Section: Discussionunclassified
“…En los últimos años, la crisis económica ha llevado a un deterioro de las condiciones laborales, también en el contexto psicosocial 11,12 . La exposición a riesgos psicosociales se ha relacionado con enfermedades cardiovasculares 13 , salud mental 14 trastornos musculoesqueléticos 15 y el consumo de alcohol y tabaco 16 .…”
Section: Introductionunclassified
“…For decades, work organisation in Spain has been based on Taylorist principles [Gonzalez Menendez, ], which has meant that a high proportion of workers are exposed to situations of lack of autonomy combined with exposure to low Demands at work. However, the rise in Psychological Demands, intensification of work, and stagnation of Control among workers in Spain has been reported in previous articles [Utzet et al, , ]. Some studies have shown that Job Insecurity is high in Spain [Moncada et al, ; Nubling et al, ].…”
Section: Introductionmentioning
confidence: 90%
“…Some studies have shown that Job Insecurity is high in Spain [Moncada et al, ; Nubling et al, ]. In a context such as the present, with high unemployment and job destruction, among those workers who have not lost their jobs Insecurity over losing valued working conditions has apparently become subordinated to Insecurity about losing the job [Moncada et al, ; Utzet et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Governments adopted austerity measures, eroding welfare states, creating widespread indignation about the loss of rights acquired when they were constituted. This aggrieved large sectors of the population (Utzet et al, 2014). Facing this economic and political crisis, many people decided to take to the streets to express their dissatisfaction, and to demand changes.…”
Section: Introductionmentioning
confidence: 99%